2020
DOI: 10.17582/journal.aavs/2021/9.2.265.273
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and Antioxidant Activity by Secondary Metabolites of Aspergillus fumigatus

Abstract: Due to the challenge faced scientists to produce the natural product as an anticancer agent from cheap sources and in endeavor to ameliorate the rate of anticancer agents, the employment of fungal metabolite in creating a cordial proper process was prerequisite. In the present study, fungal metabolites are detected by thin layer chromatography. The fungal producer strain was isolated from the rhizosphere region of old cultivated soil. One fungal isolate out of bioassay ten isolates was showed to have the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a separate study conducted recently, the bioactive metabolites of A. fumigatus, which was isolated from polluted rhizosphere soil, demonstrated cytotoxicity against HepG2 cells (Almanaa et al, 2021). In addition, the ethyl acetate extract of A. fumigatus strain MF1 which was isolated from marine soil samples found to have anticancer activity on HeLa cell lines (Kalyani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate study conducted recently, the bioactive metabolites of A. fumigatus, which was isolated from polluted rhizosphere soil, demonstrated cytotoxicity against HepG2 cells (Almanaa et al, 2021). In addition, the ethyl acetate extract of A. fumigatus strain MF1 which was isolated from marine soil samples found to have anticancer activity on HeLa cell lines (Kalyani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The components were identified by comparing the mass spectra to the mass-spectral library maintained by the National Institute of Standards and Technology (NIST 11.0, National Institute of Standards and Technology, Gaithersburg, MD, USA) and Wiley (Wiley, Chichester, West Sussex, UK) library search data during GC-MS qualitative analysis (Almanaa et al, 2021;Olivia et al, 2021).…”
Section: Gc Analysismentioning
confidence: 99%
“…has a great ability to produce a wide range of secondary metabolites which are considered a potential source of new anticancer compounds ( Kusari et al, 2009 ; El-Sayed et al, 2021 ; Noman et al, 2021 ). A study conducted by Almanaa et al (2021) reported that A. fumigates extract showed a cytotoxic effect against the HepG-2 cell line with IC 50 value of 113 μg/mL. Also, the crude extract of Aspergillus tubenginses ASH4 showed anticancer effect against HCT-116, Hep-G2, and MCF-7 with IC 50 values of 9.18, 10.41, and 5.89 μg/mL, respectively ( Elkhouly et al, 2021a , b ).…”
Section: Discussionmentioning
confidence: 99%